A biomechanical examination of the inclusion of active flexibility in artistic gymnastic movements requiring mobility - Milaim Berisha (Pedagogy of Physical Culture and Sports, 2021)
Background and Study Aim. The purpose of the study is a biomechanical examination of the inclusion of active flexibility in artistic gymnastic movements requiring mobility (muscles' ability to stretch), flexibility and other motor abilities such as force, power, etc.